Geocell strip as well as preparation method and application thereof
Through composite fiber bundle weaving and modified asphalt coating coating, the lack of performance of geogrids in complex environments is solved, and the tensile strength and durability of geogrid strips are improved. It is suitable for complex environments in civil engineering. and high load conditions.
Patent Information
- Application Number
- CN202411315133.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The existing geogrids have limited performance under complex environmental conditions, the brittleness, flexibility and high-temperature performance of a single material are insufficient, and the compatibility of composite materials is poor, resulting in limited application in civil engineering.
Weaving geogrids with composite fiber bundles (polyester filaments, carbon fibers and polyphenylene sulfide fibers) and using modified asphalt coatings (including SBS, natural rubber, polyphenylene sulfide, basalt fibers, antimony trioxide and dodecane Sodium benzenesulfonate) coated to enhance the tensile strength, durability and compatibility of the material to form geochamber strips.
It improves the mechanical stability, tear resistance and durability of geogrids, enhances the comprehensive performance of geogrid strips, and is suitable for civil engineering applications under complex environments and high load conditions.
Smart Images

Figure CN119194866A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of civil engineering materials, and in particular to a geocell strip and a preparation method and application thereof. Background Art
[0002] Geosynthetics are a type of civil engineering material that has the advantages of light weight, corrosion resistance, easy construction and good durability. They are mostly used in road engineering. The most commonly used ones include geotextiles (woven and non-woven), geogrids (biaxial and multiaxial), geocells, geonets (or geocomposite drainage products), geomembranes and geocomposites. Geocell strips are the basic building blocks of geocells. Geocell strips are formed into a grid structure by cross welding or other connection methods.
[0003] Geotextile, also known as geotextile, is a permeable geosynthetic material made of synthetic fibers through needle punching or weaving. Geotextile is one of the new geosynthetics. The finished product is cloth-like, generally 4-6 meters wide and 50-100 meters long. Geogrid is a new type of geosynthetics. The raw materials are selected from high molecular polymers and are made through extrusion, stretching or weaving. The appearance is regular pores and it is a plane structure. Geogrids include many different types, including plastic, warp knitted polyester, steel plastic, glass fiber geogrid and other main types. Existing geogrids are mostly made of a single material, such as glass fiber geogrid, warp knitted polyester geogrid, carbon fiber geogrid, etc. Although single materials have certain strength and economy, their performance is still limited under complex environmental conditions. For example, glass fiber has high tensile strength and fatigue resistance, but it is brittle and prone to microcracks under repeated loads; polyester fiber has better flexibility and ductility, but its performance decreases in high temperature environments, resulting in accelerated material aging; carbon fiber provides very high strength and rigidity, suitable for heavy-duty projects, but its production cost is high. Composite materials can combine the advantages of multiple materials and make up for the shortcomings of a single material, which is of great significance for improving the comprehensive performance of geogrids. However, the compatibility of multiple materials is not good and they are easy to disperse. Selecting a highly viscous coating to coat the composite fiber can not only coat the dispersed fibers together, but is also crucial to improving the tensile strength of the geogrid.
[0004] The combination of geogrid and geotextile to form geocell strips can better play the advantages of each, forming a multifunctional system with tensile strength, drainage, and prevention of soil loss. It has important economic and social benefits and can better meet the needs of the civil engineering industry. Summary of the invention
[0005] In view of the above-mentioned prior art, the object of the present invention is to provide a geocell strip and a preparation method and application thereof.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect of the present invention, a geocell strip is provided, which is composed of a geogrid and a geotextile, wherein the geogrid is prepared by the following method:
[0008] The composite fiber bundles are knitted into a geogrid body by using a warp knitting machine, a modified asphalt coating is applied on the geogrid body, and the geogrid is dried to obtain a geogrid;
[0009] The composite fiber bundle is formed by twisting polyester filaments, carbon fibers and polyphenylene sulfide fibers;
[0010] The modified asphalt coating is composed of asphalt, SBS, natural rubber, polyphenylene sulfide, basalt fiber, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate in a mass ratio of (70-80):(5-10):(2-5):(1-3):(2-5):(1-3):(1-2):(0.5-1.5).
[0011] Preferably, the composite fiber bundle is formed by twisting polyester filaments, carbon fibers and polyphenylene sulfide fibers in a ratio of (2-3):(2-3):(1-3).
[0012] Preferably, the modified asphalt coating is prepared by the following method:
[0013] (1) Heat the asphalt to 160-180°C, add SBS, and stir for 30-60 minutes to fully dissolve the SBS;
[0014] (2) Maintaining the temperature at 170-180°C, continue to add polyphenylene sulfide, basalt fiber and antimony trioxide, and stir for 30-60 minutes;
[0015] (3) When the temperature drops to 120-140° C., add natural rubber, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate and stir for 40-80 minutes to obtain an asphalt coating.
[0016] Preferably, the asphalt is No. 70 asphalt or No. 90 asphalt.
[0017] Preferably, the binding yarn used in weaving the geogrid is made of high-density polyethylene yarn.
[0018] Preferably, the width of the geogrid strips is 40-60 mm; the longitudinal spacing of the geogrid strips is 50-60 mm, the transverse spacing of the geogrid strips is 600-1000 mm; and the spacing between the composite fiber bundles is 1-5 mm.
[0019] Preferably, the geotextile is one of polyester (PET) geotextile, polypropylene (PP) geotextile, polyamide (PA) geotextile and polyvinyl chloride (PVC) geotextile.
[0020] A second aspect of the present invention provides a method for preparing the above-mentioned geocell strip, comprising the following steps:
[0021] The geogrid and geotextile are bonded together by adhesive or warp knitting.
[0022] The third invention of the present invention provides the use of the above-mentioned geocell strip in the preparation of geocells.
[0023] A fourth aspect of the present invention provides a method for preparing a geocell, comprising the following steps:
[0024] The geocell strips are arranged horizontally in pairs, and the adjacent geocell strips are fixedly connected by bolt connection or plug-in connection. After the combination, each cell of the geocell is a regular quadrilateral.
[0025] Beneficial effects of the present invention:
[0026] 1. The present invention weaves polyester filament, carbon fiber and polyphenylene sulfide fiber into a geogrid body. Polyester filament has the advantages of high tensile strength, good elastic modulus, chemical corrosion resistance, low creep, good temperature resistance and environmental friendliness. It is mainly used to enhance the mechanical stability of the soil in the geogrid. Carbon fiber has high rigidity and durability: carbon fiber is known for its ultra-high rigidity and strength, and is suitable for use in engineering structures that bear heavy loads. Carbon fiber can also increase the overall durability and long-term performance of the geogrid. Polyphenylene sulfide fiber has excellent chemical resistance and thermal stability: polyphenylene sulfide fiber has excellent stability at high temperatures and is suitable for geotechnical applications that may be exposed to harsh chemical and temperature environments. Polyphenylene sulfide fiber also exhibits excellent chemical corrosion resistance. Therefore, the present invention composites polyester filament, carbon fiber and polyphenylene sulfide fiber to enhance the tensile strength, wear resistance and durability of the geogrid. This combination of composite fibers provides excellent mechanical stability and tear resistance for the geogrid.
[0027] 2. The present invention also improves the asphalt coating. Adding SBS to the asphalt coating can provide excellent elasticity and durability and improve the temperature sensitivity of the asphalt; adding natural rubber can enhance the elasticity and resilience and improve the crack resistance; adding polyphenylene sulfide can improve the chemical stability and oil resistance, making it suitable for use in chemical environments; adding basalt can increase the mechanical strength and wear resistance and make it suitable for roads that bear high loads; antimony trioxide is used as a flame retardant to improve the fire resistance of the coating; polyvinyl pyrrolidone enhances adhesion and water resistance and also serves as a stabilizer; sodium dodecylbenzene sulfonate is used as an emulsifier to help emulsify the asphalt and the water phase and improve the uniformity and workability of the coating.
[0028] 3. The geogrid and asphalt coating of the present invention both contain polyphenylene sulfide. In addition to the performance improvement brought by the material itself, by adding polyphenylene sulfide fibers to the geogrid and the modified asphalt coating at the same time, the compatibility between the geogrid and the modified asphalt coating is improved, making the geogrid and the modified asphalt coating bonded more tightly. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 : Schematic diagram of the connection buckle.
[0030] Among them, 1. Plastic parts; 2. Three-hole plastic plate; 3. Plug. DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0032] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0033] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.
[0034] The SBS used in the present invention was purchased from Aeruifu (Shanghai) New Material Technology Co., Ltd., the brand is American Kraton, and the product number is D1101 A.
[0035] The polyester filament, carbon fiber and polyphenylene sulfide fiber used in the present invention are from Feicheng Lianyi Engineering Plastics Co., Ltd.
[0036] The geotextile used in the present invention is polyamide (PA) geotextile.
[0037] Example 1: Preparation of geocell strips:
[0038] (1) Preparation of modified asphalt coating:
[0039] Raw material composition: No. 70 asphalt, SBS, natural rubber, polyphenylene sulfide, basalt fiber, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are prepared in a mass ratio of 70:5:2:1:2:1:1:0.5;
[0040] Preparation method:
[0041] (a) Heat the asphalt to 170°C, add SBS, and stir for 60 min to fully dissolve the SBS;
[0042] (b) maintaining the temperature at 180° C., continuing to add polyphenylene sulfide, basalt fiber and antimony trioxide, and stirring for 60 min using a high-speed shearing machine;
[0043] (c) When the temperature drops to 120° C., natural rubber, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are added, and the mixture is stirred for 60 minutes using a high-speed shearing machine to obtain an asphalt coating.
[0044] (2) twisting the polyester filament, the carbon fiber and the polyphenylene sulfide fiber in a ratio of 3:2:1 to obtain a composite fiber bundle;
[0045] (3) The composite fiber bundles are woven into the geogrid body by a warp knitting machine. The binding yarn used in weaving the geogrid is made of high-density polyethylene yarn. The width of the geogrid strip is 50 mm. The longitudinal spacing of the geogrid strips is 55 mm, and the transverse spacing of the geogrid strips is 800 mm. The spacing between the composite fiber bundles is 2 mm.
[0046] (4) dipping the geogrid in the modified asphalt coating to ensure that the modified asphalt coating completely wraps the geogrid, rolling it so that the modified asphalt coating after extrusion is 20% of the mass of the geogrid, and drying it to obtain the geogrid;
[0047] (5) Use ZX-3 pressure-sensitive adhesive to bond the geogrid and polyamide (PA) geotextile together to obtain geocell strips.
[0048] Example 2: Preparation of geocell strips:
[0049] (1) Preparation of modified asphalt coating:
[0050] Raw material composition: asphalt, SBS, natural rubber, polyphenylene sulfide, basalt fiber, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are prepared in a mass ratio of 75:7.5:3.5:2:3.5:2:1.5:1;
[0051] Preparation method:
[0052] (a) Heat the asphalt to 170°C, add SBS, and stir for 60 min to fully dissolve the SBS;
[0053] (b) maintaining the temperature at 180° C., continuing to add polyphenylene sulfide, basalt fiber and antimony trioxide, and stirring for 60 min using a high-speed shearing machine;
[0054] (c) When the temperature drops to 120° C., natural rubber, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are added, and the mixture is stirred for 60 minutes using a high-speed shearing machine to obtain an asphalt coating.
[0055] (2) twisting the polyester filament, the carbon fiber and the polyphenylene sulfide fiber in a ratio of 3:2:1 to obtain a composite fiber bundle;
[0056] (3) The composite fiber bundles are woven into the geogrid body by a warp knitting machine. The binding yarn used in weaving the geogrid is made of high-density polyethylene yarn. The width of the geogrid strip is 50 mm. The longitudinal spacing of the geogrid strips is 55 mm, and the transverse spacing of the geogrid strips is 800 mm. The spacing between the composite fiber bundles is 2 mm.
[0057] (4) dipping the geogrid in the modified asphalt coating to ensure that the modified asphalt coating completely wraps the geogrid, rolling it so that the modified asphalt coating after extrusion is 20% of the mass of the geogrid, and drying it to obtain the geogrid;
[0058] (5) Use ZX-3 pressure-sensitive adhesive to bond the geogrid and polyamide (PA) geotextile together to obtain geocell strips.
[0059] Example 3: Preparation of geocell strips:
[0060] (1) Preparation of modified asphalt coating:
[0061] Raw material composition: asphalt, SBS, natural rubber, polyphenylene sulfide, basalt fiber, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are prepared in a mass ratio of 80:10:5:3:5:3:2:1.5;
[0062] Preparation method:
[0063] (a) Heat the asphalt to 170°C, add SBS, and stir for 60 min to fully dissolve the SBS;
[0064] (b) maintaining the temperature at 180° C., continuing to add polyphenylene sulfide, basalt fiber and antimony trioxide, and stirring for 60 min using a high-speed shearing machine;
[0065] (c) When the temperature drops to 120° C., natural rubber, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are added, and the mixture is stirred for 60 minutes using a high-speed shearing machine to obtain an asphalt coating.
[0066] (2) twisting the polyester filament, the carbon fiber and the polyphenylene sulfide fiber in a ratio of 3:2:1 to obtain a composite fiber bundle;
[0067] (3) The composite fiber bundles are woven into the geogrid body by a warp knitting machine. The binding yarn used in weaving the geogrid is made of high-density polyethylene yarn. The width of the geogrid strip is 50 mm. The longitudinal spacing of the geogrid strips is 55 mm, and the transverse spacing of the geogrid strips is 800 mm. The spacing between the composite fiber bundles is 2 mm.
[0068] (4) dipping the geogrid in the modified asphalt coating to ensure that the modified asphalt coating completely wraps the geogrid, rolling it so that the modified asphalt coating after extrusion is 20% of the mass of the geogrid, and drying it to obtain the geogrid;
[0069] (5) Use ZX-3 pressure-sensitive adhesive to bond the geogrid and polyamide (PA) geotextile together to obtain geocell strips.
[0070] Example 4: Preparation of geocell:
[0071] The geocell includes a plurality of geocell strips and a plurality of connecting buckles. The geocell pieces are arranged horizontally in pairs. The connecting buckles are used to fix the connection between the adjacent geocell pieces. After the combination, the geocells are a plurality of evenly arranged regular quadrilaterals.
[0072] The connecting buckle consists of a plastic part 1 and a three-hole plastic plate 2. There are three plugs 3 on the plastic part. The plastic part 1 and the three-hole plastic plate 2 are placed on both sides of the longitudinal node of the cell sheet. The plastic holes of the three-hole plastic plate 2 have a certain elasticity. The plugs 3 pass through the geocell strip and are fixed together with the three-hole plastic plate. Figure 1 )
[0073] Comparative Example 1:
[0074] The difference between this comparative example and Example 1 is:
[0075] The raw material composition of modified asphalt coating is as follows:
[0076] No. 70 asphalt, SBS, natural rubber, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are prepared in a mass ratio of 70:5:2:1:1:0.5.
[0077] Comparative Example 2:
[0078] The difference between this comparative example and Example 1 is:
[0079] The raw material composition of modified asphalt coating is as follows:
[0080] No. 70 asphalt, SBS, polyphenylene sulfide, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are prepared in a mass ratio of 70:5:1:1:1:0.5.
[0081] Comparative Example 3:
[0082] The difference between this comparative example and Example 1 is:
[0083] The raw material composition of modified asphalt coating is as follows:
[0084] No. 70 asphalt, SBS, basalt fiber, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are prepared in a mass ratio of 70:5:2:1:1:0.5.
[0085] Comparative Example 4:
[0086] The difference between this comparative example and Example 1 is:
[0087] The raw material composition of modified asphalt coating is as follows:
[0088] No. 70 asphalt, SBS, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate are prepared in a mass ratio of 70:5:1:1:0.5.
[0089] Test example:
[0090] (1) Test method
[0091] 1. Take the geocell strips prepared in Example 1 and Comparative Examples 1 to 4, and measure their tensile strength. The measurement method refers to GB / T 17689-2008.
[0092] 2. Refer to the literature "Zhang Mingheng. Experimental study on interlayer shear properties of carbon fiber geogrid reinforced asphalt mixture [D]. Shijiazhuang Railway University, 2022" Part 4.2-4.3 to conduct interlayer oblique shear tests on the geogrids prepared in Example 1 and Comparative Examples 1-4 (composite geotextile omitted), and record the interlayer shear displacement and interlayer shear strength.
[0093] (2) Test results
[0094] Table 1 Tensile strength test of geocell strips
[0095] Grouping Tensile strength kN / m Example 1 89 Comparative Example 1 71 Comparative Example 2 75 Comparative Example 3 73 Comparative Example 4 77
[0096] Table 2 Shear strength test of geogrid
[0097] Grouping Interlaminar shear displacement / mm Interlaminar shear strength / kPa Example 1 3.24 1758.65 Comparative Example 1 4.21 1384.59 Comparative Example 2 4.44 1508.6 Comparative Example 3 4.52 1447.2 Comparative Example 4 4.87 1465.6
[0098] It can be seen from Tables 1 and 2 that the present application uses polyester filaments, carbon fibers and polyphenylene sulfide to weave a geogrid, and the resulting geocell strips have good tensile strength. In addition, the present invention significantly improves the interlayer shear strength of the geogrid by adding natural rubber, polyphenylene sulfide and basalt fiber to the asphalt coating, and improves the bonding strength between the geogrid and modified asphalt.
[0099] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A geocell strip, characterized in that: The geogrid is composited with geotextile, and the geogrid is prepared by the following method: The composite fiber bundles are knitted into a geogrid body by using a warp knitting machine, a modified asphalt coating is applied on the geogrid body, and the geogrid is dried to obtain a geogrid; The composite fiber bundle is formed by twisting polyester filaments, carbon fibers and polyphenylene sulfide fibers; The modified asphalt coating is composed of asphalt, SBS, natural rubber, polyphenylene sulfide, basalt fiber, antimony trioxide, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate in a mass ratio of (70-80):(5-10):(2-5):(1-3):(2-5):(1-3):(1-2):(0.5-1.5).
2. The geocell strip according to claim 1, characterized in that: The composite fiber bundle is formed by twisting polyester filaments, carbon fibers and polyphenylene sulfide fibers in the ratio of (2-3): (2-3): (1-3).
3. The geocell strip according to claim 1, characterized in that: The modified asphalt coating is prepared by the following method: (1) Heat the asphalt to 160-180°C, add SBS, and stir for 30-60 minutes to fully dissolve the SBS; (2) Maintaining the temperature at 170-180°C, continue to add polyphenylene sulfide, basalt fiber and antimony trioxide, and stir for 30-60 minutes; (3) When the temperature drops to 120-140° C., add natural rubber, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate and stir for 40-80 minutes to obtain an asphalt coating.
4. The geocell strip according to claim 1, characterized in that: The asphalt is No. 70 asphalt or No. 90 asphalt.
5. The geocell strip according to claim 1, characterized in that: The material of the binding yarn used in weaving geogrid is high-density polyethylene yarn.
6. The geocell strip according to claim 1, characterized in that: The width of the geogrid strips is 40-60 mm; the longitudinal spacing of the geogrid strips is 50-60 mm, the transverse spacing of the geogrid strips is 600-1000 mm; and the spacing between the composite fiber bundles is 1-5 mm.
7. The geocell strip according to claim 1, characterized in that: The geotextile is one of polyester (PET) geotextile, polypropylene (PP) geotextile, polyamide (PA) geotextile and polyvinyl chloride (PVC) geotextile.
8. The method for preparing the geocell strip according to any one of claims 1 to 7, characterized in that: The following steps are involved: The geogrid and geotextile are bonded together by adhesive or warp knitting.
9. Use of the geocell strip according to any one of claims 1 to 7 in the preparation of geocells.
10. A method for preparing a geocell, characterized in that: The following steps are involved: The geocell strips are arranged horizontally in pairs, and the adjacent geocell strips are fixedly connected by bolt connection or plug-in connection. After the combination, each cell of the geocell is a regular quadrilateral.
